Effects of eslicarbazepine on slow inactivation processes of sodium channels in dentate gyrus granule cells. (28th June 2018) - Holtkamp, Dominik; Opitz, Thoralf; Hebeisen, Simon; Soares‐da‐Silva, Patrício; Beck, Heinz
Summary: Objective: Pharmacoresistance is a problem affecting ∼30% of chronic epilepsy patients. An understanding of the mechanisms of pharmacoresistance requires a precise understanding of how antiepileptic drugs interact with their targets in control and epileptic tissue. Although the effects of (S)‐licarbazepine (S‐Lic) on sodium channel fast inactivation are well understood and have revealed maintained activity in epileptic tissue, it is not known how slow inactivation processes are affected by S‐Lic in epilepsy. Methods: We have used voltage clamp recordings in isolated dentate granule cells (DGCs) and cortical pyramidal neurons of control versus chronically epileptic rats (pilocarpine model of epilepsy) and in DGCs isolated from hippocampal specimens from temporal lobe epilepsy patients to examine S‐Lic effects on sodium channel slow inactivation. Results: S‐Lic effects on entry into and recovery from slow inactivation were negligible, even at high concentrations of S‐Lic (300 μmol/L). Much more pronounced S‐Lic effects were observed on the voltage dependence of slow inactivation, with significant effects at 100 μmol/L S‐Lic in DGCs from control and epileptic rats or temporal lobe epilepsy patients. For none of these effects of S‐Lic could we observe significant differences either between sham‐control and epileptic rats, or between human DGCs and the two animal groups. S‐Lic was similarly effective in cortical pyramidal neurons from sham‐control and epileptic rats. Finally, we show in expression systems that S‐Lic effects on slow inactivation voltage dependence are only observed in Nav 1.2 and Nav 1.6 subunits, but not in Nav 1.1 and Nav 1.3 subunits. Significance: From these data, we conclude that a major mechanism of action of S‐Lic is an effect on slow inactivation, primarily through effects on slow inactivation voltage dependence of Nav 1.2 and Nav 1.6 channels. Second, we demonstrate that this main effect of S‐Lic is maintained in both experimental and human epilepsy and applies to principal neurons of different brain areas.